Exploring the potential of priming agents towards enhanced performance of Rubus species - Manganaris, George A.; Valanides, Nicolas; Gohari, R.; Milivojevic, J.; DeVetter, L.W.; Fotopoulos, Vasileios (My University, 2024)
The concept of the application of priming agents (PAs) to enhance yield performance and quality attributes of fruit crops is relatively novel. The process of priming involves prior exposure to biotic or abiotic stress factors rendering a plant more resistant/tolerant to future exposure. There is a wide range of compounds that are considered to have a priming effect and can be classified into the following categories: i) chemicals (i.e., hormones, reactive oxygen nitrogen and sulphur species (RONSS), and small organic molecules), ii) microorganisms (i.e., arbuscular mycorrhizal fungi (AMF) and plant growth-promoting bacteria (PGPR)), and iii) nanomaterials (i.e., organic and inorganic nanoparticles, as well as polymers). Soft fruits, also referred to as small fruits or berries, represent a wide and very diverse group of crops that have high nutritional value but are very perishable with limited shelf-life potential. These crops are also greatly affected by stress conditions. To our knowledge, the concept of priming in soft fruits is relatively new with scarce information available. The aim of the current report is dual. Initially, this report provides information regarding the prospects of priming agents as a novel agricultural and technological approach to improve stress tolerance for a range of Rubus species, namely red raspberry, blackberry, boysenberry, cloudberry, loganberry and black raspberry. Additionally, it describes the challenges and constraints of raspberry production within a global context, providing examples and case studies from the United States and Europe, two industries with striking differences in their production models.
Keywords: stress conditions; agricultural biostimulants; berries; melatonin; putrescine; raspberry production model; Rubus idaeus; sodium alginate; soft fruits